MAT PILATES EXERCISE IMPROVES STATIC BALACE OF YOUNG ADULTS WITH OBESITY - Yudha Hasya Ardana; Erna Setiawati; Rahmi Isma Asmara Putri; Yuswo Supatmo (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: The prevalence of obesity in women in Semarang at the age over 18 is 29.93%. This high prevalence rate of obesity can have a negative impact on individual health. The condition of obesity is closely related to its complications that can occur in various aspects of the body's physiology, in the example it can reduce functional abilities such as static balance which can interfere with activities and decrease quality of life. One of the methods that can be used to improve static balance is mat pilates. Mat pilates prioritizes stretching and strengthening core muscles with controlled and precise movements so that mat pilates exercises can improve static balance. However, no studies have yet discussed the effect of mat pilates exercise on static balance in obese young adults Aim: To prove that  mat pilates exercise can increase static balance of  female aged 18-23 years old with obesity. Methods: This study used quasi experimental pre and post-test design and was done in August-October 2020. The subjects were 33 female students of Medical Faculty of Diponegoro University aged 18-23 years with  BMI over 27 kg/m², divided in 2 groups. Treatment group (n=15) was instructed to do 8 weeks of mat pilates exercise (3 times a week) and control group (n=18) was instructed to not do any exercise. Static balace  was measured with Flamingo Balance Test (FBT). Data’s significance was analyzed with paired t test and independent t test. Results : There’s  a significant decrease (p<0,001; paired t test) in FBT score before and after of the mat pilates treatment group from 12,31 ± 5,15 to 10,09 ± 5,59. An insignificant increase (p=0,798; paired t test) found in FBT score before and after of the control group from 12,74 ± 4,65 to 12,93 ± 6,29. The score difference of FBT test of the mat pilates treatment group and control group shows significant result (p=0,013). Conclusion: There is an improvement of static balance after mat pilates exercise intervention on female aged 18-23 years old with obesity